Carotid Intima‐Media Thickness is Associated With Incident Heart Failure Among Middle‐Aged Whites and Blacks: The Atherosclerosis Risk in Communities Study. Issue 3 (9th May 2014) - Effoe, Valery S.; Rodriguez, Carlos J.; Wagenknecht, Lynne E.; Evans, Gregory W.; Chang, Patricia P.; Mirabelli, Maria C.; Bertoni, Alain G.
Abstract : Background: Increased carotid intima‐media thickness (IMT) is associated with subclinical left ventricular myocardial dysfunction, suggesting a possible role of carotid IMT in heart failure (HF) risk determination. Methods and Results: Mean far wall carotid IMT, measured by B‐mode ultrasound, was available for 13 590 Atherosclerosis Risk in Communities study participants aged 45 to 64 years and free of HF at baseline. HF was defined using ICD‐9 428 and ICD‐10 I‐50 codes from hospitalization records and death certificates. The association between carotid IMT and incident HF was assessed using Cox proportional hazards analysis with models adjusted for demographic variables, major CVD risk factors, and interim CHD. There were 2008 incident HF cases over a median follow‐up of 20.6 years (8.1 cases per 1000 person‐years). Mean IMT was higher in those with HF than in those without (0.81 mm±0.23 versus 0.71 mm±0.17, P <0.001). Unadjusted rate of HF for the fourth compared with the first quartile of IMT was 15.4 versus 3.9 per 1000 person‐years; P <0.001. In multivariable analysis, after adjustment, each standard deviation increase in IMT was associated with incident HF (HR 1.20 [95% CI: 1.16 to 1.25]). After adjustment, the top quartile of IMT was associated with HF (HR 1.60 [95% CI: 1.37 to 1.87]). Results were similar across race and gender groups. Conclusions: Increasing carotid IMT is associated with incident HF in middle‐aged whites and blacks, beyond risks explained by major CVD risk factors and CHD. This suggests that carotid IMT may be associated with HF through mechanisms different from myocardial ischemia or infarction.